PENGARUH EFEK TERATOGENIK TERHADAP KEJADIAN PENYAKIT JANTUNG BAWAAN: ARTICLE REVIEW - Putra, Bayu Pratama; Palaguna, Sriwati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Congenital heart disease (CHD) is a dangerous condition with an estimated 50% death in the first month of birth. This condition is often caused by the teratogenic effects of drug exposure at a young age during gestation. This is associated with the process of heart formation during organogenesis in pregnancy. There are 10 articles reviewed and show a significant influence between teratogenic drugs and CHD.Keywords: Teratogenic effects, organogenesis, congenital heart disease, CHD.